Remote sensing techniques for archaeology: A state of art analysis of SAR methods for land movement - Kosta, Alexandra; Paraskevopoulos, Ioannis; Agapiou, Athos; Battistin, Fabiana; Serpetti, Matteo; Waldoch, Filip; Rączkowski, Włodzimierz; Di Iorio, Alessio; De Angeli, Stefano; Hadjimitsis, Diofantos G. (My University, 2020)
The RESEARCH project (Remote Sensing techniques for Archaeology; H2020-MSCA-RISE, 2018-2022, grant agreement: 823987) addresses the design and development of a multi-task platform, combining advanced remote sensing technologies with Geographical Information System (GIS) application for mapping and long-term monitoring of Archaeological Heritage (AH) at risk, to identify changes due to climate change and anthropic pressures. The Earth Observation (EO) processing chain will address significant risks affecting AH including soil erosion, land movement and land-use change. The paper describes one of the main goals of RESEARCH project. It refers to a state of the art analysis of Synthetic Aperture Radar (SAR) methods applied to the land movement detection such as landslide and subsidence. Satellite SAR is a rapidly evolving remote sensing technology that offers a high potential for detecting, documenting and monitoring heritage targets. Satellite SAR interferometry (InSAR), Differential Interferometry (DinSAR) and Persistent Scatterer Interferometry (PSI) are different techniques that, depending on the available data and the required accuracy, can be used for deformation monitoring of AH.
Keywords: Archaeological heritage; Interferometry; Land movement; Synthetic Aperture Radar (SAR)